Einblicke in die Entstehung von Mikrotubuli: Cytoskelett - Pfeffer, Stefan; Schiebel, Elmar (Biospektrum, 2020)
Microtubules are part of the cytoskeleton and promote various essential cellular functions. Microtubules are dynamic polymers composed of heterodimeric α/ß-tubulin subunits and can assemble de novo in a ‘structural templating’ mechanism assisted by ring-like complexes containing the protein γ-tubulin. Recent cryo-electron microscopy structures of such γ-tubulin ring complexes from vertebrates propelled our understanding of their architecture, assembly and activation mechanism.